Masa Depan Demokrasi Mesir Pasca-Arab Spring - Maskum, Ahmad Baihaqi; Machmudi, Yon (Jurnal ICMES, 2023)
This research discusses the progress of democracy in Egypt after the Arab Spring. When the Arab Spring expanded in the Middle East to Egypt, it was considered the beginning of a transition towards a country managed by the concept of democracy. The Arab Spring, which has been in turmoil since early 2011, has become the beginning of the rise of a mass movement to demand changes in the socio-political order. The Arab Spring in Egypt was initially expected to create a democracy that guaranteed equality and social justice. However, Egypt has failed to implement democracy and is left behind in almost all sectors of life, including economy. Instead of democracy, what is happening in Egypt is praetorianism, namely the military that dominates state decision-making, and frozen democracy, namely the freezing of a democratic political system that has developed due to various existing restrictions.